2022
DOI: 10.53730/ijhs.v6ns1.5690
|View full text |Cite
|
Sign up to set email alerts
|

Elevated serum levels of interleukin -22 and interleukin-23 in pediatric asthma

Abstract: Background: There are few studies had addressed the association between serum levels of Interleukin -22 and Interleukin-23 with severity of asthma, this study aims to evaluate whether elevated IL-22 and IL-23 serum levels is related to the severity of asthma. Methods: This study is a case-control study that included 60 asthmatic children (35 male and 25 female) as the patients group age ranged between 4 months to 14 years old, and 60 non-asthmatic (32 male and 28 female) age-matched patients group attending th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…IL-23's effect on serum IgE level is unclear due to controversial results of experiments on serum IL-23 and IgE association. According to Manti and others, a positive correlation was observed between serum levels of IL-23 and IgE, while another study suggested non-significant negative correlation and no significant association [26].…”
Section: Th17 Cells and Armentioning
confidence: 88%
“…IL-23's effect on serum IgE level is unclear due to controversial results of experiments on serum IL-23 and IgE association. According to Manti and others, a positive correlation was observed between serum levels of IL-23 and IgE, while another study suggested non-significant negative correlation and no significant association [26].…”
Section: Th17 Cells and Armentioning
confidence: 88%